Praktik Khiyar pada Jual Beli Tiket Transportasi dalam Tinjauan Hukum Ekonomi Syariah di Mandailing Natal - Hamid, Asrul (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2023)
Khiyar is defined in Islamic teachings as a form of option right given by the seller to the buyer to continue or cancel a sale and purchase transaction with the aim of causing pleasure so that a sense of satisfaction is created between the two parties and there is no dispute in the future. Sometimes buyers feel dissatisfied with the goods being traded due to unknown problems that require the buyer to cancel purchases made previously, as was the case in buying and selling transportation tickets in Mandailing Natal Regency. This research is a field research with an analytical descriptive approach, namely describing the phenomena that occur and then analyzing it so that the results of the research are obtained. The results of this study can be concluded that the practice of khiyar in buying and selling transportation tickets in Mandailing Natal Regency is not fully in accordance with the principles of Islamic teachings, even though the khiyar provisions regarding ticket cancellation have been stipulated in the ticket, the provisions are not yet in accordance with the concept of muamalah and the provisions are not conveyed to the buyer ticket when a sale and purchase transaction occurs.